A Systematic Review Experimental And Numerical Studies Of Fire Influence On Lateral Resistance And Buckling Performance Of Cold Formed Steel Sections - Cheah, Yue Yeou (Universiti Sains Malaysia, 2021)
This study presents the review on the critical objectives on the influence of fire on lateral resistance and buckling performance of cold-formed steel (CFS) sections and the methods of conducting the study onto both criteria. More fire safety regulations and countermeasures are needed due to the losses caused by fire events worldwide. Likewise, the use of CFS is expanding recently to industries and mid-rise buildings. This condition required accurate prediction of the buckling behaviour and parameters affecting the lateral resistance of CFS sections in the fire. Even though many studies were related to buckling performance and lateral resistance, they were not discussed directly and clearly. Yet, there are several sections of steel with different effects when exposed to fire. In this review work, it can be observed that the experimental approaches used in this study were described in terms of its specimen preparation, equipment used, and type of test used. On the other hand, the numerical approaches were described in terms of design standards and analysis software used. At last, the influence of fire on CFS sections was discussed.